Full Day School di Madrasah Ibtidaiyah Nurul Ummah Kotagede - Heru Prasetyo (eL Bidayah: Journal of Islamic Elementary Education, 2023)
Currently, the madrasah has an important role in fostering students by holding positive and beneficial activities for the future, then the full-day school system emerged which was finally widely applied in Indonesia. This full-day school aims to foster attitudes or morals and form better character in students amid the rampant moral decadence of the nation's children, this program is also accompanied by the provision of religious values because students have a lot of time in the madrasah, so coaching will be easily done by the madrasah. This study aims to determine the implementation of a full-day school that has been implemented by MI Nurul Ummah Kotagede. The type of research used is qualitative research with descriptive methods. Data collection was done by observation and interviews. Data processing and analysis techniques used are data reduction techniques, presentation, and conclusions. The results showed that the implementation of a full-day school at MI Nurul Ummah in the learning process lasted for 9 hours per day. Covering religious activities and other public lessons then complemented by extracurriculars to support the interests and talents of students [Saat ini madrasah memiliki peran penting dalam membina peserta didik dengan mengadakan kegiatan-kegiatan yang positif dan bermanfaat untuk masa depan, kemudian muncul sistem full day school yang akhirnya diterapkan secara luas di Indonesia. Sekolah sehari penuh ini bertujuan untuk membina sikap atau akhlak dan membentuk karakter yang lebih baik pada siswa di tengah maraknya dekadensi moral anak bangsa, program ini juga dibarengi dengan pemberian nilai-nilai religi karena peserta didik memiliki banyak waktu di madrasah , sehingga pembinaan akan mudah dilakukan oleh pihak madrasah. Penelitian ini bertujuan untuk mengetahui implementasi full day school yang telah dilaksanakan oleh MI Nurul Ummah Kotagede. Jenis penelitian yang digunakan adalah penelitian kualitatif dengan metode deskriptif. Pengumpulan data dilakukan dengan observasi dan wawancara. Teknik pengolahan dan analisis data yang digunakan adalah teknik reduksi data, penyajian dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pelaksanaan full day school di MI Nurul Ummah dalam proses pembelajaran berlangsung selama 9 jam per hari. Meliput kegiatan keagamaan dan pelajaran umum lainnya kemudian dilengkapi dengan ekstrakurikuler untuk menunjang minat dan bakat siswa]